The Classroom Teachers' Strategies In Character Formation Responsible at Grade III of SD Negeri 15 Padang - Riswanti, Novia; Efrina, Gusnita; Oktira, Yona Syaida; Azwar, Rica (The Future of Education Journal, 2024)
This study is aimed at analyzing the Strategies of Class Teachers in Responsible Character Formation in Class III Elementary School State 15 Padang. This research uses a qualitative approach with a descriptive type. Data is then collected through observations, interviews, and documentation, followed by data analysis through three stages: data reduction, data presentation and conclusion drawing. The subjects of this study are third-class teachers and pupils. This research was carried out at Elementary Shool State 15 Padang in January-February 2024. The results of the research show that, the strategy of class teacher in the formation of character responsible in class III  Elementary School State 15 Padang is by giving motivation and compatibility of teachers, student active retention in learning, customization, giving sanctions to students who violate,train students' responsibility to the class